2007
DOI: 10.1017/s0007114507381397
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary soyabean meal, inulin and oxytetracycline on intestinal microbiota and epithelial cell stress, apoptosis and proliferation in the teleost Atlantic salmon (Salmo salar L.)

Abstract: Soyabean meal (SBM)-induced enteritis in the distal intestine of the teleost Atlantic salmon (Salmo salar L.) and other salmonids may be considered a model for diet-related mucosal disorders in other animals and man. The role of the intestinal microbiota in its pathogenesis was explored. Compared to diets containing fishmeal (FM) as the sole protein source, responses to extracted SBM or the prebiotic inulin, with or without oxytetracycline (OTC) inclusion, were studied following a 3-week feeding trial. Intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
215
7
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 318 publications
(256 citation statements)
references
References 75 publications
(120 reference statements)
33
215
7
1
Order By: Relevance
“…Soybean meal in rainbow trout diets produces welldocumented deleterious effects on the distal intestine, such as morphological changes and subacute enteritis [12][13][14][15][16][17][18][19], as well as changes to intestinal microbial communities [15,16,18], and hepatic morphology [12]. Similar effects have been reported in Atlantic salmon Salmo salar [20][21][22][23].…”
Section: Introductionmentioning
confidence: 75%
“…Soybean meal in rainbow trout diets produces welldocumented deleterious effects on the distal intestine, such as morphological changes and subacute enteritis [12][13][14][15][16][17][18][19], as well as changes to intestinal microbial communities [15,16,18], and hepatic morphology [12]. Similar effects have been reported in Atlantic salmon Salmo salar [20][21][22][23].…”
Section: Introductionmentioning
confidence: 75%
“…To the authors' knowledge there is very little information regarding the effect of prebiotics on carnobacteria within the GI tract of fish. However, some studies suggest that the carnobacteria populations within the GI tract of salmonids are effected by various dietary factors such as krill meal [32] and oxytetracycline [29] in Atlantic salmon and dietary carbohydrates in Arctic charr (Salvelinus alpinus L.) [19,35]. However, it was observed that the presence of dietary inulin (a prebiotic-type carbohydrate) tended to lower culturable autochthonous carnobacteria levels (by ca.…”
Section: Discussionmentioning
confidence: 99%
“…have often been reported to be components of the gut microbiota of salmonids; indeed, C. maltaromaticum, C. mobile, C. divergens and Carnobacterium spp. have been identified from Atlantic salmon [29][30][31][32][33]. The consistency of isolation of these species indicates that these might be common core components of the GI microbiome of Atlantic salmon and are likely to be of importance to the host.…”
Section: Microbiota Of Fish Fed Control Diet and Intestines Exposed Tmentioning
confidence: 92%
See 2 more Smart Citations